Semantic change found in the news articles of Republika - Mia Perlina; Umi Hani (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
This study aimed to analyze the types and factors that cause changes in meaning of certain words. 10 news articles were chosen as the data that were taken from Republika, a national online newspaper in Indonesia. To collect and analyze the data, this study involves several steps, among others are skimming to find out the words undergoing semantic change, classifying the words into several types of semantic change proposed by Hollman (2009a),  finding out the causes of semantic change based on Chaer’s (2009) framework, and drawing a conclusion based on the result of the study. The results showed that there were 48 words undergoing semantic change, and these words were then classified into 6 types of semantic changes, namely generalization, specialization, amelioration, pejoration, metaphor, and metonymy. In addition, all the words undergoing semantic change were motivated by several factors, including association, field of use, the development of lexical item use, socio-cultural factor, and ellipsis. This study is expected to be contributed to the field of semantics, both in the teaching-learning process and the research study on semantics. Besides, the result of this study may become one of the references for those who are interested in how the language is used in journalism.